Employing lipase of candida antarctica (calb) as catalyst in the acetylation of para-aminophenol in aqueous and water-free medium - Hilda Ismail; Evi Lande Setiyani; Dwi Titus Indriyawati; B. S. Ari Sudarmanto (Jurnal Teknosains, 2021)
Candida antarctica lipase B (CaLB) is one of lipase classes enzymes that has many advantages to be used in the process of synthesizing organic compounds. In this study, some experiments were conducted to examine the ability of CaLB as a catalyst in the para-aminophenol (PAP) acetylation to produce paracetamol as the result. Two types of research have been carried out, the first one is to utilize CaLB to catalyze acetylation of PAP in a water-free reaction medium, and the second one is to use CaLB as catalyst in aqueous medium through oxidative amidation reaction. Reaction in water free system was held in ethyl catalyst acetate as solvent that also act as the acyl donor, while in the aqueous medium, acetylacetone was used as acyl donor and ethyl acetate as source to produce peracid that will be used as oxidator. Analysis was done by HPLC and TLC densitometric to follow the amount of paracetamol produced.  The results of CaLB-catalyzed acylation in water free system showed that the enzyme could accept PAF and ethyl acetate as a substrate in a nucleophilic substitution reaction, resulting in paracetamol as a product. However, the yield from the acylation of PAP is still not satisfactory. In the reaction in aqueous medium, CaLB has been proven to show its activity to catalyze the acylation of PAP with acetylacetone, as well as the reaction of peracid formation from ethyl acetate. The results show that this strategy can work well and give better yields than the other reaction in water-free medium.